Serotype specificity and immunogenicity of the capsular polymer of Haemophilus pleuropneumoniae serotype 5. - Inzana, T J (1987)
Serotyping of Haemophilus pleuropneumoniae and serologic assays for detection of serotype-specific antibody are problematic due to the potential cross-reactivity of the crude antigens used for raising immune serum or for serology. The capsular polymer (CP) of H. pleuropneumoniae serotype 5 was investigated for serotype-specific activity with antiserum to whole cells or with antiserum made monospecific to CP by adsorption with a capsule-deficient mutant. When antiserum to whole cells or monospecific antiserum to CP was tested against purified CP from serotypes 1 to 7 by immunodiffusion or enzyme-linked immunosorbent assay, only capsules of serotype 5 were reactive. In addition, only encapsulated serotype 5 cells reacted with serum monospecific to CP in an indirect immunofluorescent-antibody assay. Serotype-specific antibody was completely inhibited in each assay by preincubation of purified CP with the serum. Antiserum to whole cells of H. pleuropneumoniae serotype 5 contained antibodies to proteins and lipopolysaccharide; these antibodies cross-reacted with antigens of heterologous serotypes by dot-blot enzyme-linked immunosorbent assay and immunoblotting. The antigenic activity of CP was stable after heating for at least 30 min at 100 degrees C. High titers of antibody to CP were present in the sera of rabbits immunized intravenously with whole log-phase cells or in the convalescent sera of pigs experimentally infected with H. pleuropneumoniae serotype 5. However, the purified CP was poorly immunogenic in rabbits and swine. Our results indicate that the capsule is the serotype-specific antigen of H. pleuropneumoniae and that a monospecific antiserum to capsule or purified capsule should be used for serotyping or serologic assays, respectively.